COVID-19: Technology-Supported Remote Assessment of Pediatric Asthma at Home - van der Kamp, Mattienne R.; Tabak, Monique; de Rooij, Sophia E. J. A.; van Lierop, Pieter P. E.; Thio, Boony J. (Frontiers in Pediatrics, 2020)
The COVID-19 crisis has pressurized hospital based care for children with high-risk asthma, as they have become deprived of regular clinical evaluations. However, COVID-19 also provided important lessons about implementing novel directions for care. Personalized eHealth technology tailored to the individual and the health care system could substitute elements of hospital care and facilitate early and appropriate medical anticipation in response to imminent loss of control. This perspective article discusses new approaches to clinical, organizational and scientific aspects of the use of eHealth technology in paediatric asthma care in times of COVID-19.